Neonatal Rupture of the Spleen: Successful Treatment with Splenic Artery Embolization - Jelle W. Raats; Lievay van Dam; Pieter J. van Doormaal; Marjoleine van Hengel-Jacobs; Hester Langeveld-Benders (Thieme Medical Publishers, Inc., 2021)
Neonatal intra-abdominal hemorrhage has been rarely reported in the literature. We report a case of splenic injury in a neonate, highlighting the importance of a high-index suspicion in early recognition of this rare and potentially fatal injury. We report the first case of a neonate who had a splenic rupture and underwent successful endovascular treatment.